2019
DOI: 10.1145/3306607
|View full text |Cite
|
Sign up to set email alerts
|

Status Quo in Requirements Engineering

Abstract: Context: Requirements Engineering (RE) has established itself as a software engineering discipline over the past decades. While researchers have been investigating the RE discipline with a plethora of empirical studies, attempts to systematically derive an empirical theory in context of the RE discipline have just recently been started. However, such a theory is needed if we are to define and motivate guidance in performing high quality RE research and practice. Objective: We aim at providing an empirical and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 53 publications
0
36
0
1
Order By: Relevance
“…All techniques are discussed in the following subsections (2)(3)(4)(5)(6)(7). Quality characteristics are discussed in subsection 8, whereas tools and datasets are discussed in subsection 9.…”
Section: ) Summary Of Primary Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All techniques are discussed in the following subsections (2)(3)(4)(5)(6)(7). Quality characteristics are discussed in subsection 8, whereas tools and datasets are discussed in subsection 9.…”
Section: ) Summary Of Primary Studiesmentioning
confidence: 99%
“…However, natural languages are prone to semantic and synaptic errors, as they do not adhere to a complete formal semantic grammar [S62, S63]. Consequently, requirements written in a textual form, such as initial requirements or user stories [3], are prone to errors that may lead to unacceptable systems. Additionally, the requirements specified in other diagrammatic notations, such as use cases [S15], sequence diagrams [S21], and behavior interaction diagrams [S08], are difficult to comprehend by nontechnical users.…”
Section: Introductionmentioning
confidence: 99%
“…This deeper examination of the context of the requirements is behaviour we would expect to reduce the requirements fixation that Mohanani et al (2014) identified that can occur as a result of requirements framing and our observations support this. Taking this broader perspective, attempting to understand a richer context of the requirements, is behaviour that we would expect to move these teams in a favourable direction with respect to the widespread cause of project failure identified by NaPiRE (Wagner et al, 2019) as being incomplete requirements.…”
Section: ) Playing the Short Or The Long Game -Individual And Team Hmentioning
confidence: 99%
“…RE is a Team Sport and Human Factors are Key NaPiRE notes that after 40 years of research and practice, the discipline of RE still struggles, despite significant contributions made over those years in the form of tools, methods, and process (Wagner et al 2019). As noted earlier, NaPiRE surveys indicate that many organisations in industry adopt these RE methods and even they still report the most common cause of project failure being incomplete requirements.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation